1994
DOI: 10.1021/bi00189a049
|View full text |Cite
|
Sign up to set email alerts
|

TSG-6, an Arthritis-Associated Hyaluronan Binding Protein, Forms a Stable Complex with the Serum Protein Inter-.alpha.-inhibitor

Abstract: TSG-6 is a secreted 35-kDa glycoprotein, inducible by TNF and IL-1. The N-terminal portion of TSG-6 shows sequence homology to members of the cartilage link protein family of hyaluronan binding proteins. The C-terminal half of TSG-6 contains a so-called CUB domain, characteristic for developmentally regulated proteins. High levels of TSG-6 protein are found in the synovial fluid of patients with rheumatoid arthritis and some other arthritic diseases. Here we show that TSG-6 readily formed a complex with a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
112
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 25 publications
5
112
1
Order By: Relevance
“…The antiinflammatory properties of Tnfip6 have been mainly attributed to its ability to potentiate the antiplasmin activity of I␣I upon association with this protease inhibitor, leading to the subsequent downregulation of the activity of a number of matrixdegrading proteases (7)(8)(9)(10). However, a recent study (11) found that the isolated Link module domain of Tnfip6, which lacks the ability to associate with I␣I, could still inhibit the influx of neutrophils to the site of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The antiinflammatory properties of Tnfip6 have been mainly attributed to its ability to potentiate the antiplasmin activity of I␣I upon association with this protease inhibitor, leading to the subsequent downregulation of the activity of a number of matrixdegrading proteases (7)(8)(9)(10). However, a recent study (11) found that the isolated Link module domain of Tnfip6, which lacks the ability to associate with I␣I, could still inhibit the influx of neutrophils to the site of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of the Tnfip6-I␣I complex appears to be specific for plasmin, since no increase was observed in the inhibitory activity against other serine proteases (10). Since plasmin is a key activator of matrix-degrading metalloproteases, it has been postulated that Tnfip6 exerts its antiinflammatory and chondroprotective effects through the inactivation of the metalloprotease network (7,9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fractions 5-15 of the third gradient, no band was detected at the positions corresponding to ITI (180 kDa), P␣I (120 kDa), and the covalent ITI/TSG-6 complex (120 kDa) by Coomassie Blue staining and immunostaining. TSG-6 (tumor necrosis factor-stimulated gene 6), an inflammatory HABP of 35 kDa, has been shown to be present in synovial fluid of patients with rheumatoid arthritis and some other forms of arthritis but not in normal human joints (25). Interestingly, this molecule in the patient synovial fluid has been found to form a covalent complex with ITI molecules via the chondroitin sulfate chains (25).…”
Section: Discussionmentioning
confidence: 99%
“…TSG-6 is known to form a stable, $120 kDa, complex with inter-a-inhibitor (IaI), a 180 kDa serine protease inhibitor found in serum [23,31]. IaI-TSG-6 complexes of this size have been detected in the synovial fluids of arthritis patients [30].…”
Section: Introductionmentioning
confidence: 99%